Surface Characterization and Platelet Adhesion on Thin Hydrogel Films of Poly(vinyl ether) - Itagaki, Nozomi (Langmuir : the ACS journal of surfaces and colloids, 2017)
Poly(vinyl ether), with short oxyethylene side chains which possess a simple and relatively polar structure, should be a unique candidate for a bioinert material thanks to its solubility in water. On the basis of living cationic copolymerization and subsequent ultraviolet light irradiation, thin films of poly(2-methoxyethyl vinyl ether) with different cross-linking densities were prepared on solid substrates. The films were thickened in water, and the extent was dependent on the cross-linking density. Although the surface chemistry and aggregation states were almost identical to one another, the stiffness, or the softness, of the outermost region in the film was strongly dependent on the cross-linking density. That is, the interface between polymer and water became thicker, or more diffused, with decreasing cross-linking density. The blood compatibility based on the platelet adhesion on to the hydrogel films was better for a more diffused interface